"EL TORO” GOLD MINE (PERU): GEOLOGICAL FEATURES AND PERSPECTIVES - Villena, Н. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
El Toro is an epithermal gold deposit with an epizonal conformation being hosted in the clastic sediments of lower Cretaceous (Chimu Formation). The ore deposit is located in La Libertad Region in northern Peru. Spatially it configures an elongated geometry that aligns with the Andes mountain ridges; geomorphologically it is a 1.0 x 1.5 km dome structure. The dome axis is formed by a subvolcanic intrusion of dacite / andesite composition (20–18 Myr), the basement deposit consists of pelitic rocks, slate, shales and carbonaceous slimes of Chicama Formation. They are underlain by clastic sequences of Goyllarisquizga Group conformed to quartz and laminar sandstones. Locally, four tectonic events (ET) are recognized: ET-2 (overthrust faults), ET-4 (NW-SE faults), ET-5 (high angle NW-SE faults) and ET-6 (annular faults). Mineralization in oxides constitutes 80% of current mineral resources and is related to sedimentary rocks, tectonic breccia, hydrothermal breccia, collapse breccia and oxidized dacite blocks; while sulfides and mixed materials are restricted to dacite/andesite bodies. The resource estimation results performed in 2014 (NI 43-101 Resources Technical Report, El Toro gold project) determine: 65,000 gold ounces of measured resources, 27,600 gold ounces of indicated and 398,000 gold ounces of inferred resources. According to projection and based on the interpretation and correlation of structural styles , lithological domains and similar ore deposits, approximately 1,500 km2 demarcation is outlined (El Toro-Altagracia, proposal of a new mining district).This preliminary interpretation is also based on analogical correlation with other mining districts with similar genesis and resources that would surpass in total thirty million gold ounces.
Keywords: epithermal gold deposit; clastic sediments mineralization; mining district; lithological and structural interpretation; 3D geologic modeling